Periodical oscillation of particle-laden laminar flow within a tubular photocatalytic hydrogen production reactor predicted by discrete element method. (26th February 2021) - Geng, Jiafeng; Tang, Junwang; Cai, Wenfang; Wang, Yechun; Jing, Dengwei; Guo, Liejin
Abstract: Besides their wide existence in various industrial processes, nanoscale particle suspensions are also the important media for some emerging technologies such as photocatalytic hydrogen production. The circulating flow properties of the nanoparticles in the fluid are of great concern for their practical use. In our study, a modified experimental system was set up based on Malvern laser particle analyzer that can estimate the nanoparticle concentration and size distribution in a laminar nanoparticle circulating flow. We found that the particle concentration and size distribution were periodical oscillation with time in such flow. Understanding the oscillation mechanism is capable of promote the energy efficiency of photocatalytic hydrogen production. A simulation based on Discrete Element Method (DEM) was conducted to understand this particular oscillation mechanism by studying the single particle movement and trajectory properties in the solid-liquid suspension. The simulation results agree well with the tendency obtained by the experimental results and are capable of better understanding the oscillation characteristics. The simulation results also reveal that the nanoparticles tend to gather in the middle region (the higher velocity region) of the tube after several cycles. Moreover the gravity is of great significance in the circulating flow of solid-liquid suspension because the particle swarms tend to distribute a little below the axial center line of the straight tube. These obtained results are credible for understanding the nanoscale particle transport phenomenon in many natural or industrial processes. In particular, our results are helpful for the understanding and effective control of the movement and distribution of photocatalyst particles in the tubular photocatalytic reactor, which is believed to significantly affect the incident radiation distribution and finally the energy conversion efficiency of the photocatalytic process. Highlights: A simulation based on DEM method is conducted to predict the particles transport; A periodical oscillation of the particles volume fraction and size is predicted; The trajectory and behaviour of single particle was studied by the simulation; This simulation can be extended to other applications of particulate system.